2003
DOI: 10.1093/bja/aeg217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of end-tidal and transcutaneous measures of carbon dioxide during general anaesthesia in severely obese adults

Abstract: Transcutaneous carbon dioxide monitoring provides a better estimate of Pa(CO(2)) than FE'(CO(2)) in patients with severe obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 15 publications
2
28
1
4
Order By: Relevance
“…fusion mismatching. 4,17 In this study, we focused on accuracy of P ETCO 2 measurement using a capnometry-type oxygen mask in subjects without a past medical history of pulmonary disease.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…fusion mismatching. 4,17 In this study, we focused on accuracy of P ETCO 2 measurement using a capnometry-type oxygen mask in subjects without a past medical history of pulmonary disease.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…In the present study, the TC-CO 2 continuously increased within 30 min after midazolam injection and decreased after flumazenil injection. Previous studies have reported a linear correlation between PaCO 2 and TC-CO 2 [6][7][8]. Bendjelid [9] reported that evaluation of PaCO 2 data on the basis of TC-CO 2 values was clinically acceptable, although the relationship between TC-CO 2 and PaCO 2 varies in patients breathing spontaneously in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…However, a transcutaneous device is used for continuous noninvasive monitoring of PaCO 2 [6]. Previous studies have demonstrated a linear correlation between PaCO 2 and transcutaneous CO 2 (TC-CO 2 ) [7][8][9]. The results of TC-CO 2 monitoring are independent of air leakage [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is the original idea when we carried out the experiment. We synthesized PetCO 2 local production of carbon dioxide in the tissue, which leads to falsely high measurements [14]. On the contrary, PetCO 2 measurement was always underestimated compared with PCO 2 because gas from lung units that were ventilated but not perfused (alveolar dead space or high ventilation-perfusion ratio units) contains little or no carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the early studies, neither PetCO 2 nor PtcCO 2 monitoring has provided accurate estimates of PaCO 2 [13][14][15] …”
Section: Introductionmentioning
confidence: 99%